Local scour due to water jet from a nozzle with plates - Kartal, Veysi; Emiroglu, M. Emin (Springer Int Publ Ag, 2021)
In this study, local scour occurring downstream from a nozzle with and without plates formed in cohesionless materials was investigated experimentally. The experiments were performed to determine scour geometry, maximum scour depth, and the effect of aeration on scour for water jets impinged obliquely into the downstream pool. Dimensionless variables affecting the scour were determined as densimetric Froude number, dimensionless impingement length, and the ratio of densimetric Froude number to dimensionless impingement length. Experiments were conducted for three nozzle diameters with plates, three nozzle diameters without plates, two different impingement lengths, and three different exit velocities. The results of the experiments showed that the use of the plates in the nozzle, jet impact velocity, jet shape, jet expansion, jet impingement length, and air entrainment rate were critical parameters for scour geometry. As a result, it was found that the jets from a nozzle with plates entrained more air bubbles into the impingement pool than jets from nozzles without plates, thereby decreasing maximum scour depth by spreading the scour over a larger area. This was evident by increasing the impingement length. In addition, scour equations were obtained to determine maximum scour depth, ridge height, and scour hole length from experimental data.
Keywords: Water jet; Scour; Downstream pool; Bed sediment layer; Nozzle; Plates; Aeration